Main currents in early Christian thought - Barr, Robert R. (Guide to the Fathers of the church, 1., 1966)
Basing himself on a solid knowledge of patrology, the author seeks to indicate the great themes of thought in the Fathers of the Church. In this sense his book furnishes a very sure guide for one who wishes to orient himself in the vast realm of patrology. More than that, he indicates the main problems the Fathers faced and how these were resolved. He simultaneously enables the reader to find what the Fathers of the Church are able to give us that is essential, and what belongs to a specific method of thought.